Management of pedagogical supervision and teacher performance in the teaching of English in Peru - Sánchez Castro, Angélica (2021)
This research was done to determine the relationship between supervision and teacher practice in an English teaching center with a high student population in Lima Perú. This is a quantitative approach basic type study with a non-experimental transversal design where 5 and 7 point Likert-type-scale questionnaires were used to provide data that was analyzed with descriptive and inferential statistics. A non-probabilistic sample of intention or convenience was used to select the respondents. 210 teachers from different branches in Lima were selected to respond to the questionnaires. A descriptive analysis of the statistics was used to interpret the results on the supervisors functions and the teacher performance level in each one of the study areas after the supervisory service had been offered. To contrast the data for the hypothesis test to determine the relationship between supervision and teaching performance (content knowledge of the discipline, teaching skills, contextual knowledge, learner-focus teaching, professionalism), the Spearman correlation coefficient was used. A direct, meaningful and high correlation level was found. The results of the current study will benefit other English language centers management to implement changes and improvements to the supervision service that will result in better teaching performance and student achievement.